Youth as Social Service Consumers: the Case of Russia - Alevtina V. Starshinova; Olga I. Borodkina; Elena B. Arkhipova (Social Work & Society, 2021)
The formation of a mixed system of public goods production in Russia has been accompanied by the increasing role of the private sector in the field of social services, characterized by innovative approaches to the provision of youth services. This paper presents the results of a study aimed at the following key questions: what the place of youth in the social service system is, and what the attitude of youth to state social services and NGOs is. Empirical data were obtained from surveys of residents of St. Petersburg and Yekaterinburg (n = 1204), among which almost 40% of participants were young respondents aged between 18 and 35. The questionnaire included questions about the demand for social services, relationships to NGOs as service providers, the prevalence of receiving services using digital technologies, the issuers concerning the quality of social services, and trust/distrust of NGOs.  Different client groups among youth and development trends were identified. The research results indicate the prevalence of young respondents who are confident that new providers can expand the range of social services and improve their quality. Young people showed a high level of satisfaction with the services they received from non-governmental organizations, and they believe that NGOs are more client-oriented, then governmental organizations. The study demonstrates that youth is becoming one of the key actors in the developing system of mixed-welfare provision in Russia, which is more consistent with the modern views on young people as consumers of social services and which is able to attract them to the service market as providers.